Stigmatization Of ODHIV In The Working Area Of PB Health Center Selayang II Medan In 2023 - Elisa Sisca Sembiring; Donal Nababan; Frida Lina Tarigan (SEAN Institute, 2023)
Stigma is a negative label that is a sign for someone given by someone else or yourself. Stigma is influenced by the environment and becomes a barrier for that person to get attention, opportunities and social interaction and becomes one of the inhibiting factors in improving the quality of life of PLHIV. The purpose of this research is to find out the life story, stigma and its impact, and the factors that influence acceptance of stigma. This type of research is qualitative research and data collection uses the interview method. The informants in this study were divided into 2, namely 4 key informants and 4 respondents as triangulation informants. The results of this study indicate that there is a life story effect with the causes of key informants being exposed to HIV. Stigma obtained by key informants can be categorized into several levels of stigma, namely self-stigma, family/community stigma and also institutional stigma. Furthermore, there are 2 factors that affect the acceptance of stigma for PLHIV, namely external factors and also internal factors. Based on this, it is suggested to the family that it can be a place where children can get education and love. People also need to understand more about HIV so that stigmatization can be reduced. Medical personnel must also improve services for people living with HIV so that they can also get proper services, and the local government must be able to assist HIV-related programs so that they can run smoothly.